Soundness of the Heart: An Analysis of the Unique Qualities of the Qalb Salīm - Abu Bakr Sirajuddin Cook; Salih Yucel (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2022)
Within Islam, the topic of the heart (qalb) occupies an important place. In order to understand the breadth and depth of this topic, it is necessary to understand its intricacies. The Qur’ān, the Ḥadīth, and scholarly interpretations detail the potentialities that, to varying degrees, lie dormant within each and every individual. The heart is described as being able to be pure and to find peace, while equally being able to be darkened and rust. The qalb is mentioned frequently throughout the sacred texts of Islam. This article examines the notion of qalb salīm, mentioned twice within the Qur’ān, both times with regard to the Prophet Ibrahim. Firstly, the importance of qalb will be elaborated. Secondly, an examination of the qalb salīm within the major Qur’ānic commentaries (tafsīr), particularly Sufi exegesis, is examined. Thirdly, related ḥadīth literature is analyzed. An attempt is made to understand the soundness of a sound heart. The analysis in this article will highlight the qualities associated with the qalb salīm. While a comprehensive analysis of the notion of qalb salīm is beyond the scope of this article, an attempt is made to open further discussion on this important concept and address the dearth of currently available academic literature.